STRATEGI BAURAN PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN IKAN TUNA OLAHAN PADA PT. BETEL CITRA SEYAN GORONTALO - Zainal Abidin Umar (Jurnal Inovasi, 2012)
This research aimed to describe and analyze marketing mix aspects toward the selling volume of processing tuna fish at PT Betel Citra Seyan Gorontalo.The research was carried out at PT Betel Citra Seyan Gorontalo. The method used in this research was case study, whereas, the collected data were then analyzed by means of descriptive and Strength Weakness Opportunity Threat (SWOT) analyses.The result of the research indicated that: (1) the aspects of marketing mix covering product, price, distribution and promotion related simultaneously to the sale volume of processing tuna fish at PT Betel Citra Seyan Gorontalo; (2) the marketing mix aspects including quality, type, and kinds of products were partially related to the sale volume of tuna fish. The purchasing price of raw materials and source of raw materials from the fishermen influenced the selling volume, whereas, the role of promotion less influenced the selling volume; and (3) the marketing mix strategy which was required to be conducted by PT Betel Citra Seyan Gorontalo was intensive strategy or integrated strategy.